LncRNA‐ATB promotes viability, migration, and angiogenesis in human microvascular endothelial cells by sponging microRNA‐195. Issue 9 (15th April 2019) - Zhu, Ai‐Dong; Sun, Ying‐Ying; Ma, Qiu‐Ju; Xu, Fei
Abstract: The atherosclerosis in the arterial system of the extremities is considered as the major pathogenesis of peripheral arterial disease. The present work aimed to explore the potential role of long noncoding RNA activated by tumor growth factor‐β (lncRNA‐ATB) on the dysfunction of endothelial cells. Human microvascular endothelial cells (HMEC‐1) were transfected with lncRNA‐ATB expressing vectors, and then the formation of tubes and expression of proteins associated with angiogenesis were analyzed using microscope and reverse transcription‐quantitative polymerase chain reaction (RT‐qPCR)/Western blot analysis. Cell viability, migration, and microRNA‐195 (miR‐195) expression were examined by Cell Counting Kit‐8 assay, modified Boyden chambers, Western blot analysis, and RT‐qPCR. The interaction between lncRNA‐ATB and miR‐195 was determined by RT‐qPCR, dual‐luciferase reporter assay, and biotin‐avidin pull‐down assay. Finally, expression of key kinases in the PI3K/AKT and MEK/ERK pathways was determined by Western blot analysis. We found vascular tubulogenesis was induced spontaneously when HMEC‐1 cells were cultured in Matrigel‐coated plates. lncRNA‐ATB overexpression increased cell viability, migration and formation of tubes, along with upregulation of matrix metalloproteinase‐2 (MMP‐2), MMP‐9, and vascular endothelial growth factor. Then, we found lncRNA‐ATB worked as a molecular sponge for miR‐195, and the effects of lncRNA‐ATB on HMEC‐1 cells were reversed by miR‐195 overexpression while were augmented by miR‐195 inhibition. Phosphorylated levels of key kinases in the PI3K/AKT and MEK/ERK pathways were increased by lncRNA‐ATB via miR‐195. In conclusion, lncRNA‐ATB enhanced cell viability, migration and angiogenesis in HMEC‐1 cells through sponging miR‐195. Moreover, the PI3K/AKT and MEK/ERK pathways were activated by lncRNA‐ATB via miR‐195. Abstract : Long noncoding RNA activated by tumor growth factor β (lncRNA‐ATB) enhanced cell viability, migration, and angiogenesis in HMEC‐1 cells through downregulating microRNA‐195 (miR‐195). Moreover, the PI3K/AKT and MEK/ERK pathways were activated by lncRNA‐ATB via miR‐195.